Dried blood spot sampling in combination with LC-MS/MS for quantitative analysis of small molecules - Li, Wenkui; Tse, Francis L. S. (Biomedical chromatography, 2010)
The collection of whole blood samples on paper, known as dried blood spot (DBS), dates back to the early 1960s in newborn screening for inherited metabolic disorders. DBS offers a number of advantages over conventional blood collection. As a less invasive sampling method, DBS offers simpler sample collection and storage and easier transfer, with reduced infection risk of various pathogens, and requires a smaller blood volume. To date, DBS‐LC‐MS/MS has emerged as an important method for quantitative analysis of small molecules. Despite the increasing popularity of DBS‐LC‐MS/MS, the method has its limitations in assay sensitivity due to the small sample size. Sample quality is often a concern. Systematic assessment on the potential impact of various blood sample properties on accurate quantification of analyte of interest is necessary. Whereas most analytes may be stable on DBS, unstable compounds present another challenge for DBS as enzyme inhibitors cannot be conveniently mixed during sample collection. Improvements on the chemistry of DBS card are desirable. In addition to capturing many representative DBS‐LS‐MS/MS applications, this review highlights some important aspects of developing and validating a rugged DBS‐LC‐MS/MS method for quantitative analysis of small molecules along with DBS sample collection, processing and storage. Copyright © 2009 John Wiley & Sons, Ltd.